Antenatal care practice and pregnancy out come at Kudat area,Sabah,Northern Borneo - Tin, Tin Aye; Datuk Muhammad Yusof Ibrahim; Daw, Khin Saw Naing; Than Myint; Muhammad Hj Jical (Bangladesh Journals OnLine (BanglaJOL), 2017)
Women have been fulfilling their reproductive responsibility of propagating human race, many have died and many more faced death in the process of delivering babies, but this can be prevented by taking appropriated antenatal care, clean and safe delivery and essential obstetric care. Antenatal care is the first phase to be encountered once a woman has conceived. The objective of the study was to assess the antenatal (AN) care practice and pregnancy outcome of ever-married women aged 18 to 49 years old having at least one pregnancy experience, residing in kampongs of Kudat area, Sabah, East Malaysia, Northern Borneo from December 2015 to October 2016. Crosssectional analytical study, non-probability convenient sampling method was used and 300 eligible participants were interviewed face to face by trained interviewer using pretested questionnaire. 99.3% of all the women received AN care, and 97% of the women received AN care practice (AN visit of 4 times and above). Mean AN visit was 9 times. The study revealed that overall knowledge amongst the women with good knowledge was 47.2% and low knowledge was 52.8%. Additionally, there was significant association between education and knowledge, income and knowledge, AN care practices and knowledge. But there was no significant association between AN practice and complication. Despite these results, outcomes were good and all complications were properly and successfully addressed. This may reflect the effectiveness of current national maternal health programs.